A CASE STUDY OF PSYCHOSOCIAL IMPACT IN ENURETIC GIRL ADOLESCENT - Erni Agustina Setiowati (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2012)
The aim of this article is to describe psychososial consequences in girl adolescent with nocturnal anddiurnal enuresis or mixed enuresis. Qualitative research method is used in this study. An-13-year-oldfemale presented with severe mixed enuresis since 4th grade. Data were collected by observation,interview, and psychological testing. Observation conducted in school and home setting. Interviewconducted on parent, siblings, friends, and teacher. The result showed that subject’s interpersonalrelationship quality is less, less self-confident, ashamed, more irritable, and being bullied